2021
DOI: 10.1109/access.2021.3054919
|View full text |Cite
|
Sign up to set email alerts
|

Political Arabic Articles Orientation Using Rough Set Theory With Sentiment Lexicon

Abstract: Sentiment analysis is an emerging research field that can be integrated with other domains, including data mining, natural language processing and machine learning. In political articles, it is difficult to understand and summarise the state or overall views due to the diversity and size of social media information. A number of studies were conducted in the area of sentiment analysis, especially using English texts, while Arabic language received less attention in the literature. In this study, we propose a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 40 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…The results showed that using TF with TF-IDF improved the accuracy to a good ratio. In [17], The researchers conducted artificial neural network-based emotion classification using a dataset of 2,122 sentences from 206 Arabic documents. They also employed this method to categorize people's opinion posts into three groups: conservative, revolutionary, and reform.…”
Section: Related Workmentioning
confidence: 99%

Evaluation of Different Stemming Techniques on Arabic Customer Reviews

Hawraa Fadhil Khelil,
Mohammed Fadhil Ibrahim,
Hafsa Ataallah Hussein
et al. 2024
JT
“…The results showed that using TF with TF-IDF improved the accuracy to a good ratio. In [17], The researchers conducted artificial neural network-based emotion classification using a dataset of 2,122 sentences from 206 Arabic documents. They also employed this method to categorize people's opinion posts into three groups: conservative, revolutionary, and reform.…”
Section: Related Workmentioning
confidence: 99%

Evaluation of Different Stemming Techniques on Arabic Customer Reviews

Hawraa Fadhil Khelil,
Mohammed Fadhil Ibrahim,
Hafsa Ataallah Hussein
et al. 2024
JT
“…RST play a good role in SA via several languages in several applications such as political articles orientation [25] and political polarity detection [26], these researches using English and Arabic lexicon with RST. RST-based give a good results in Arabic/English sentiment analysis text.…”
Section: Rough Set Theory (Rst)mentioning
confidence: 99%
“…SVM is used extensively for ASA in the literature, as in [18,40,56]. In this work, SVM with sigmoid kernel was used according to the following equations [57]:…”
Section: Support Vector Machinementioning
confidence: 99%